2017
DOI: 10.1111/jdv.14391
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab demonstrates greater sustained improvements in daily activities and personal relationships than ustekinumab in patients with moderate‐to‐severe plaque psoriasis: 52‐week results from the CLEAR study

Abstract: BackgroundPsoriasis can greatly impact patients’ lives by influencing clothing worn as well as by impairing sexual functioning. Secukinumab, a human monoclonal antibody selectively neutralizing interleukin‐17A, has demonstrated good efficacy and safety in the treatment of moderate‐to‐severe psoriasis and psoriatic arthritis with a rapid onset of action and sustained response.ObjectiveThis analysis using the CLEAR study, a phase 3b double‐blind study comparing the efficacy and safety of secukinumab vs. ustekinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…[15][16][17][18][19][20] The 52-week results from a phase IIIb, head-tohead, randomized, multicenter, CLEAR (NCT02074982) study demonstrated the superior efficacy of secukinumab versus ustekinumab in clearing skin of subjects with moderate to severe plaque psoriasis, with greater improvement in health-related quality of life and a comparable safety profile. [21][22][23][24] In this study, 9.2% of the total randomized subjects were of Asian origin. Despite the limited population, given that the moderate to severe form of psoriasis is less prevalent in the Asian population, a subgroup analysis from CLEAR study would be beneficial in understanding the efficacy and safety profile of secukinumab in this cohort.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…[15][16][17][18][19][20] The 52-week results from a phase IIIb, head-tohead, randomized, multicenter, CLEAR (NCT02074982) study demonstrated the superior efficacy of secukinumab versus ustekinumab in clearing skin of subjects with moderate to severe plaque psoriasis, with greater improvement in health-related quality of life and a comparable safety profile. [21][22][23][24] In this study, 9.2% of the total randomized subjects were of Asian origin. Despite the limited population, given that the moderate to severe form of psoriasis is less prevalent in the Asian population, a subgroup analysis from CLEAR study would be beneficial in understanding the efficacy and safety profile of secukinumab in this cohort.…”
Section: Introductionmentioning
confidence: 78%
“…Further, efficacy and safety analyses were explored up to week 52 as key secondary objectives. Both the primary and the secondary objectives have been reported separately . The focus of this subgroup analysis was to evaluate the efficacy and safety of secukinumab treatment compared with ustekinumab in Asian subjects with moderate to severe plaque psoriasis from the CLEAR study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unter SCK gewinnen die Patienten offenbar schneller an Lebensqualität im Vergleich zu UTK. Weitere Untersuchungen sind hier notwendig [85].…”
Section: Auswahl Klinischer Und Diagnostischer Ergebnisse Bei Psaunclassified
“…After the era of successful use of biologics in psoriasis, kinase inhibitors are coming. The Janus‐kinase inhibitors like tofacitinib are powerful agents in modulating T‐cell responses.…”
mentioning
confidence: 99%